The Influence of Learning Strategies and Learning Environment on the Difficulties of Learning Economics in Grade X Students - Muhamad Juaini; Mispandi (Journal of Educational Studies, 2025)
This study aims to determine the influence of learning strategies and the learning environment on difficulties in learning economics.This study employed a quantitative research method with a descriptive design. The study population was 175 tenth-grade students of SMAN 1 Sakra Timur. The sample size was 35 students, selected using a proportional sampling technique. The data collection technique and instrument used in this study was a questionnaire. Data were analyzed using validity tests, reliability tests, autocorrelation tests using the runs test method, multiple linear regression tests, multiple correlation tests, the coefficient of determination (R2) test, partial t-tests, and simultaneous f-tests, using SPSS version 26 software.The results of this study indicate that, partially, there is no significant influence between the variables of learning strategies and the learning environment on difficulties in learning economics. This is evidenced by the calculated t-value < t-table (0.762 < 2.037) for the learning strategies variable, and the calculated t-value < t-table (-1.267 < 2.037) for the learning environment variable. And there is no significant influence between learning strategies and learning environments on the difficulty of learning economics (Y). Proven by the F-count value < F-table (0.833 < 3.29) with a significance value of 5%. It can be concluded that learning strategies and learning environments do not have a significant influence on the difficulty of learning economics. It can be concluded that learning strategies and learning environments do not have a significant influence on the difficulty of learning economics in this context. These findings should nevertheless be interpreted with caution given the very low explanatory power of the model (Adjusted R² = -0.010), suggesting that the difficulty students experience in learning economics is more strongly determined by factors outside the two predictors examined here, such as students' prior knowledge, motivation, and cognitive load.